Synthesis and Adsorption of Ni(II) on Ni(II)-Imprinted Polyaniline Supported on Attapulgite Modified with 3-Methacryloxypropyltrimethoxysilane - Hui Xu; Jing Tang; Lin Tan; Wei Wang; Hailin Lu; Donghong Guo (Adsorption Science & Technology)
A novel Ni(II) ion-imprinted polymer [Ni(II)–IIP] was prepared by surface-imprinting technique using aniline as the functional monomer and 3-methacryloxypropyltrimethoxysilane (MPS)-modified attapulgite as the support material. The prepared sorbents were characterized by Fourier transmission infrared spectra, BET and scanning electron microscopy. The adsorption experiments carried out using Ni(II)–IIPs were optimized by changing the length of the polymer, contact time, solution pH, the concentration of template ion and the amount of cross-linking agent, etc. In addition, batch experiments were performed to evaluate adsorption kinetics and adsorption isotherms. The study results revealed that Ni(II)–IIPs had higher adsorption capacity and higher recognizing ability for Ni 2+ compared with non-imprinted polymers. The experimental data fitted well with both the pseudo-second-order kinetic model and the Langmuir model. The maximum theoretical adsorption capacity for Ni 2+ ions is 123.61 mg/g. The relative selectivity factor values of Ni(II)–IIPs for adsorbing Ni 2+ /Cu 2+ , Ni 2+ /Hg 2+ and Ni 2+ /Cr 2 O 7 2– are 80.94, 31.68 and 5.29, respectively. In addition, the decrease in the adsorption capacity of Ni(II)–IIPs is negligible after reusing several times.